ANALISIS STRATEGI DAN UPAYA PEMERINTAH YANG INOVATIF UNTUK MEWUJUDKAN PROGRAM DESA UNGGUL DAN KEBERLANJUTAN - Rinata Putri, Briza; Salahudin (MAJAPAHIT POLICY, 2021)
The people in Indonesia have the right to obtain the same facilities and infrastructure and have the obligation to take part in the people's welfare efforts organized by the government. This is one of the government's policies in the development of social welfare. In essence, the basic needs of the Indonesian people such as clothing, food, housing, health, and education must be met. To obtain all of this, the guarantee of comfort and security in an area is very necessary and is the main factor for the continuity of comfortable and safe village life. However, seeing the different conditions of every human being, some of them do not have public awareness in protecting and maintaining the surrounding environment. This requires us as fellow human beings to create an effort to restore public awareness of the environment we live in and its surroundings. Based on the problems above, this has led to speculation that the government is not paying attention to improving environmental welfare so that this problem will not go away. This study aims to determine the role of the government in supporting the level of public awareness of the welfare of the surrounding environment and to show the impact that occurs. This research approach is carried out with qualitative research methods, then the data used is secondary data that the authors get from the official website of the Ministry of Health.go.id as well as government report documents or previous journals. Data were analyzed using Nvivo 12 plus. The results of the study indicate that the efforts made by the village government to increase awareness of environmental welfare in rural communities by collecting village potential or available resources in the village. In addition to the village community, the government, the private sector, and activists also play a very important role in efforts to increase environmental health awareness and this research is carried out to form a superior and sustainable village. The limitation of this research is that the data used is still very limited.